Caldecott favorites featuring The snowy day, Antarctic antics, Make way for ducklings --and more! [videorecording (DVD)] - Lithgow, John, 1945-; Dern, Laura; Whitfield, Lynn; Keats, Ezra Jack; Keats, Ezra Jack; Keats, Ezra Jack; Keats, Ezra Jack; Keats, Ezra Jack; Keats, Ezra Jack; Keats, Ezra Jack; Sierra, Judy; Aruego, Jose; et al. (Scholastic storybook treasures., 2011)
The Ezra Jack Keats collection. Snowy day: One winter morning Peter wakes up to see that snow has fallen, covering everything in the city! What exciting adventures will be have on this snowy day? Whistle for Willie: Wouldn't it be great if Peter could whistle for his dog, Willie? He tries hard, but he can't make a sound. Peter's chair: A little sister means big trouble for Peter, first his parents paint his cradle pink, and then they paint his crib! But he won't let them paint his chair! Pet show!: Archie wants to enter his cat in the neighborhood pet show, but his cat has vanished! What will he do? A letter to Amy: Peter is having a birthday party and he sends a special invitation to a special friend. Will Amy show up? The trip: Louie moves to a new neighborhood and he is lonely without his friends, so he enters a magical world of imagination and flies back to his old home. Apt. 3: One rainy day, Sam hears the sad sounds of a harmonica. He searches the building to find the source and meets a new friend.